HRSG system description and water-steam analysis at the hrsg cold start-up - Strušnik, Dušan (JET on-line, 2021)
The basic purpose of this paper is to present the HRSG system description in detail and possibility analysis of preventing the HRSH water-steam generated release into the atmosphere through the sky valves during the HRSG cold start-up. The steam released into the atmosphere by the cross sky valve is not an adequate solution for the following reasons: Noise prevention, water losses, thermal heat release into the environment, etc. In this paper, the possibilities and solutions are investigated in order to avoid the HRSG start-up sky venting. For this purpose, the steam quality data at HRSG cold start-up is analysed, and the possibility is examined of discharging the HRSG generated steam at the start-up via a new start-up pipeline into the existing dump condenser, or into the start-up flash tank or into the blowdown tank. The results show that, at the first 3 minutes of cold start-up, the HRSG generated only water, and this water should not be discharged into the HP or IP pipeline headers. The HRSG generates a mixture of water and steam only after 4 minutes from the start-up. For that reason it is not recommended to drain the water-steam mixture at the HRSG start-up into the new start-up pipeline, but it is recommended to drain the water and steam mixture formed during the HRSG start-up into the new start-up flash tank, or into the blowdown tank. The flash tank, and also the blowdown tank, should be appropriately dimensioned.
Keywords: boiler; duct; flue gas; heat recovery; stack; steam generator; superheater